Stillness in motion in the seventeenth-century theatre - Skantze, P. A., 1957- (Routledge studies in Renaissance literature and culture ;, 2003)
P.A. Skantze argues that 17th century writers for performance portray a crucial aesthetic tension between motion and fixity, the study argues that this tension is fundamental to our scholarly understanding of performance and culture.